2000
DOI: 10.24266/0738-2898-18.3.132
|View full text |Cite
|
Sign up to set email alerts
|

Response of Five Woody Landscape Plants to Primo and Pruning

Abstract: The use of Primo (trinexapac-ethyl) was investigated as an alternative to pruning of container-grown woody ornamental species. A foliar spray of 469, 938, or 1407 ppm (0.5, 1.0 or 1.5 oz/gal) was applied to pruned plants. A nontreated control (water) and an industry control [Atrimmec (dikegulac-sodium)] were also included for comparison. Monthly mechanical pruning or no pruning treatments were imposed during the production period. Monthly pruning alone reduced the height of euonymus, forsythia, Chinese privet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to Cline [1996Cline [ , 1997, dikegulac can act as an anti-auxin, like 2,3,5-triiodobenzoic acid (TIBA), which blocks auxin translocation and reduces the apical dominance. Dikegulac most probably inhibits gibberellin biosynthesis by inhibiting the oxidation of ent-kaurene to ent-kaurenic acid [Thetford and Berry 2000]. Such a hypothesis is supported by the fact that its action is counteracted by GA 3 [Bocion and de Silva 1977].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to Cline [1996Cline [ , 1997, dikegulac can act as an anti-auxin, like 2,3,5-triiodobenzoic acid (TIBA), which blocks auxin translocation and reduces the apical dominance. Dikegulac most probably inhibits gibberellin biosynthesis by inhibiting the oxidation of ent-kaurene to ent-kaurenic acid [Thetford and Berry 2000]. Such a hypothesis is supported by the fact that its action is counteracted by GA 3 [Bocion and de Silva 1977].…”
Section: Discussionmentioning
confidence: 93%
“…In 2007, any legal use of dikegulac ended in EU member countries [Rademacher 2015]. However, it has been tested especially in micropropagation of woody plants [Thetford and Berry 2000, Pozo et al 2004, Sansberro et al 2006, Mendoza-de Gyves et al 2008, Sarropoulou et al 2014, Sun et al 2015, Antonopoulou at al. 2018.…”
mentioning
confidence: 99%
“…Also, early studies on peas (Pisum sativum L.) have shown that the action of dikegulac is counteracted by GA 3 (Bocion, de Sil- va 1977). Moreover, the decrement in some woody species of shoot length was ascribed to the inhibition of gibberellin biosynthesis due to dikegulac addition by inhibiting oxidation of ent-kaurene to entkaurenic acid, which is a prerequisite for gibberellic acid biosynthesis (Thetford, Berry 2000). Hence, since dikegulac inhibits gibberellin biosynthesis, its inclusion in the nutrient medium at low doses could have similar results to chemical pinching, while at higher concentrations it inhibits shoot growth.…”
Section: Resultsmentioning
confidence: 99%